Dampak Pengabdian Kepada Masyarakat Terhadap Pengembangan Pariwisata: Studi Kasus di Bali, Indonesia - Annisa Rizkikaddhuhani; I Wayan Bratayasa (PENTAHELIX: Jurnal Ilmiah Pengabdian Pariwisata, 2023)
Community service has become an essential aspect of sustainable tourism development, especially in developing countries where tourism is a significant source of revenue. This study aims to examine the impact of community service on tourism development in Bali, Indonesia. Using a case study approach, data were collected from various sources, including interviews with tourism stakeholders, community leaders, and tourists. The findings show that community service initiatives have a positive impact on tourism development in Bali. These initiatives contribute to the improvement of local infrastructure, the preservation of cultural heritage, and the promotion of eco-tourism activities. Moreover, community service projects increase community involvement in tourism, enhance community pride and ownership, and foster a sense of responsibility towards sustainable tourism development